The Trinidad and Tobago Marine Police Launch ''Seahawk'' on patrol off Port of Spain harbour. (1960)
This is an image of the Trinidad and Tobago Marine police launch ''Seahawk'' on patrol off Port of Spain harbour.
Good Condition
This image is not digitized.
This image is available on the Special Collections Floor.
Keywords: Trinidad. -- Photographs. -- Jamaica; Photograph